2020
DOI: 10.1108/jerer-12-2019-0051
|View full text |Cite
|
Sign up to set email alerts
|

Do intrinsic rewards matter for real estate agents?

Abstract: Purpose Rewards’ management has long been used as a panacea to promote job satisfaction and labour retention. However, the relationship between these variables is not clearly defined in the real estate industry, due to the scarcity of empirical studies. The purpose of this study is to evaluate the role of both satisfaction with intrinsic rewards (SIR) and satisfaction with extrinsic rewards (SER) on job satisfaction and turnover int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 44 publications
(34 reference statements)
6
37
3
Order By: Relevance
“…The findings of their study showed that intrinsic rewards related positively with satisfaction with the organization and intentions to stay at both time periods, with programs supportive of employee innovation further enhancing employee satisfaction and retention more strongly during the change effort. Furthermore, Mosquera et al (2020) evaluated the role of satisfaction with intrinsic rewards in the three largest real estate agencies in Portugal. The results of their study indicated that intrinsic rewards have a positive and significant impact on the job satisfaction of the employee.…”
Section: Literature Review and Hypotheses Development Intrinsic Rewards And Performance Of Employeesmentioning
confidence: 99%
“…The findings of their study showed that intrinsic rewards related positively with satisfaction with the organization and intentions to stay at both time periods, with programs supportive of employee innovation further enhancing employee satisfaction and retention more strongly during the change effort. Furthermore, Mosquera et al (2020) evaluated the role of satisfaction with intrinsic rewards in the three largest real estate agencies in Portugal. The results of their study indicated that intrinsic rewards have a positive and significant impact on the job satisfaction of the employee.…”
Section: Literature Review and Hypotheses Development Intrinsic Rewards And Performance Of Employeesmentioning
confidence: 99%
“…Despite, there are mixed findings on real estate pricing in general; some studies reveal that pricing behaviour is asymmetric (Annamalai et al , 2014; Cheng et al , 2019; Filotto et al , 2018), some studies found symmetric pricing behaviour of Covid-19 pandemic shock is also assumed to be an obstruction to the global economy which may be driven the negative expectation of investors’ income on HPI and could be further explained by rockets and feathers effects in support of the uneven movement of pricing behaviour. Obviously, series of studies investigated HPI from different perspectives due to undisputable contributions of real estate sector to the growth and development of national economy in particular and global economy in general (Annamalai et al , 2014; Apergis, 2015; Barros et al , 2012; Jadevicius and Gool, 2020; Mosquera et al , 2020; Tanrivermiş, 2020) and changes in the housing market could be dramatically observed (Kaya et al , 2019). Furthermore, findings on housing pricing behaviour remain inconclusive, therefore, related studies on asymmetric and symmetric of real estate pricing level discussed in the next two subsequent sections.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…House price index (HPI) is a real estate related financial asset and real estate sector contributes substantially to the economic growth and development of several countries such as Turkey economy (Kaya et al , 2019; Tanrivermiş, 2020), Australia economy (Gholipour et al , 2019; Wang et al , 2017), India economy (Annamalai et al , 2014), Portugal economy (Mosquera et al , 2020) and Netherland economy (Jadevicius and Gool, 2020). In general, the role of real estate sector is indispensable to the economy of any nation (Abidoye et al , 2019) and becoming essential investment tool for individuals and administrations (Kaya et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers adapted the questionnaire by dividing it into three sections for each variable. The reward system variable section consists of three items (Mosquera et al, 2020) followed by 17 items in the employee engagement section using three dimensions: vigor, dedication, and absorption. In addition, two items in the employee satisfaction section consist of two dimensions: ob performance and satisfaction (Mosquera et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The employees tend to work more effectively if their pay is adjusted to performance. However, financial rewards are not the only way to motivate employees to achieve higher levels of performance (Mosquera et al, 2020). Yoon et al (2015) stated that extrinsic rewards can make employees work creatively.…”
Section: Reward Systemmentioning
confidence: 99%